Evaluasi Kapabilitas dan Perancangan Tata Kelola TI Menggunakan COBIT 2019: Sekretariat Kabinet - Ontoreza, Afrianda Gaza; Wirani, Yekti; Sucahyo, Yudho Giri (AI Society & STMIK Indonesia, 2024)
E-government is the utilization of ICT applications to provide government services that enhance service delivery to be transparent, efficient, and effective. In Indonesia, the policy for managing e-government is regulated through Presidential Regulation No. 95 of 2018 concerning the Electronic-Based Government System (SPBE). This study was conducted in the Cabinet Secretariat (Setkab) with an SPBE evaluation results index that can still be optimized, particularly for the governance domain, which achieved a score of 2.90. Organizationally, Setkab does not yet have an information technology governance document. The research aims to conduct an evaluation of the capability level and formulate IT governance recommendations using COBIT 2019 framework. Assessment and design are carried out in accordance with Setkab's objectives, 13 processes are identified that are still below organizational expectations or below maturity level 3. IT governance recommendations are formulated to support the organization's strategic plan and increase the SPBE achievement index at Setkab.